On the Relationship between Foreign Direct Investment and Energy Consumption: The Mexican Case - Aali-Bujari, AlÃ; Venegas-MartÃnez, Francisco (International Journal of Energy Economics and Policy, 2021)
This paper is aimed at analyzing the interrelation between Foreign Direct Investment (FDI) and Energy Consumption (EC) in Mexico during the period 1970-2014. To do that, we carry out a cointegration test and a Granger causality analysis. The empirical results from the cointegration test show a stable link between the growth rates of FDI and EC in the long run. While the results from Granger's causality show that in the short run there is a unidirectional Granger causality from the growth rate of FDI toward the growth rate EC, while in the medium and long there is a bidirectional causality between the growth rates of FDI and LEC in Mexico during the period under study. Keywords: foreign direct investment, energy consumption, cointegration, Granger causality JEL Classifications: C32, F21, Q43. DOI: https://doi.org/10.32479/ijeep.10988